A retrospective study of cases of canine demodicosis submitted to a commercial diagnostic laboratory servicing the United Kingdom and Ireland (2017–2018): Part 1 – Signalment, lesion distribution, treatments, and concurrent diseases. (31st December 2022) - Kelly, Pamela A.; McKay, Jennifer S.; Maguire, David; Jones, Matthew; Roberts, Larry; Powell, Frank; Breathnach, Rory
Abstract: Canine demodicosis, due to an overpopulation of Demodex spp. mites, remains one of the most common dermatological diseases encountered in small animal practice. The aims of this study were to interrogate submitted histories and diagnostic report results from a large cohort of dogs ( n  = 508) diagnosed with demodicosis either through histological analysis or the finding of Demodex spp. mites on skin scrapings by a UKAS accredited commercial laboratory servicing the United Kingdom (UK) and Ireland in the years 2017 and 2018. The main findings revealed that short-coated breeds were more likely to develop juvenile-onset (JO) demodicosis, whereas medium- and long-coated breeds were more likely to develop adult-onset (AO) disease. Pododemodicosis was reported more commonly in adult, long-coated breeds. Skin scrapings were positive in only 83.3% of samples that had a corresponding positive biopsy result; this finding highlights the necessity to perform further diagnostic tests if demodicosis remains clinically suspected despite a negative skin scraping result. Concurrent underlying diseases, potentially associated with immunosuppression, were reported in 42/221 (19%) of dogs with AO demodicosis. Serum allergy and Sarcoptes ELISA assays were positive in individual animals in both the JO and AO groups; the clinical significance of these latter findings requires careful interpretation in dogs with confirmed demodicosis. Highlights: Short-coated dogs are more likely to develop JO demodicosis, whereas medium- and long-coated dogs were more likely to develop AO disease. Pododemodicosis is more common in adult, long-coated dog breeds than short-coated dog breeds. It is necessary to perform further diagnostic tests if demodicosis is clinically suspected despite a negative skin scraping result.